Tamaño y reproducción de la raya Dasyatis longus (Pisces: Dasyatidae), en Bahía Almejas , Baja California Sur, México - Villavicencio Garayzar, Carlos J (Universidad de Costa Rica, 1994)
Males and females of the elasmobranch fish Dasyatis longus reached a size of 98 and 156 cm DW, respectively in Baja California Sur. Males matured al 80 cm DW and females al 110 cm. There were 1-3 young per brood and neonates were 40 cm DW in spring-summer.